2013
DOI: 10.1021/cb400317x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Fe(III) Heme Binding to Cysteine-Containing Heme-Regulatory Motifs in Proteins

Abstract: Regulatory heme binds to specific motifs in proteins and controls a variety of biochemical processes. Several of these proteins were recently shown to form complexes with ferric and/or ferrous heme via a cysteine residue as axial ligand. The objective of this study was to examine the heme-binding properties of a series of cysteine-containing peptides with focus on CP motif sequences. The peptides displayed different binding behavior upon Fe(III) heme application with characteristic wavelength shifts of the Sor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
116
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 70 publications
(133 citation statements)
references
References 46 publications
16
116
1
Order By: Relevance
“…4A) compared with free hemin (λ max = 385 nm). Similar absorption patterns (λ max = 412-417 nm) have been reported for heme binding to peptides with a single cysteine residue (14) and to proteins with Cys/His coordination (Table S1). Heme binding to a control peptide B (LPFESSKKATGVQSKPINRKQPGRFALDNFE) in which Cys and His residues have been replaced did not show any evidence of heme binding under the same conditions.…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…4A) compared with free hemin (λ max = 385 nm). Similar absorption patterns (λ max = 412-417 nm) have been reported for heme binding to peptides with a single cysteine residue (14) and to proteins with Cys/His coordination (Table S1). Heme binding to a control peptide B (LPFESSKKATGVQSKPINRKQPGRFALDNFE) in which Cys and His residues have been replaced did not show any evidence of heme binding under the same conditions.…”
Section: Resultssupporting
confidence: 77%
“…In the case of ion channel regulation, it has recently emerged that there is a role for heme (12,(23)(24)(25)(26), but the observations are largely empirical, so that the molecular basis for the regulatory control within individual channel proteins has yet to be properly defined. A number of heme-responsive motifs (27) have been suggested to be involved: these include Cys/Pro (CP) motifs using thiolate ligation to the heme as in the P450s or Cys/His motifs (3,14). In the case of the Slo1 channels (12), a cytochrome c-like CXXCH motif has been implicated (12,28).…”
Section: Discussionmentioning
confidence: 99%
“…A number of heme-binding interactions have been suggested, including Cys/Pro (CP) motifs or Cys/His motifs (66,(68)(69)(70).…”
Section: Discussionmentioning
confidence: 99%
“…To further characterize the nature of the heme-MSP3 complex, we first quantitatively measured heme binding by two independent methods (17) and found that MSP3 can bind 35-40 mol of hemin/mol of protein. Such multiple heme-binding sites present in a protein sequence are often attributed to high histidine content or due to the presence heme regulatory motifs (61)(62)(63). For example, histidine-rich protein II that has high histidine content can bind 35-50 mol of heme/mol of protein (17).…”
Section: Discussionmentioning
confidence: 99%